Interpretivist Tradition in Qualitative Anthropological Research Writings - Upadhyay, Prakash (Himalayan Journal of Sociology and Anthropology, 2012)
Stranded in a philosophical position, qualitative research is fundamentally “Interpretivist” in the sense that it is concerned with how the social world is realized, interpreted, understood and experienced, or produced. Qualitative investigation based researches rummage around for answers to their questions in the realistic world. They congregate what they see, hear and read from the people and places and from events and activities and their main purposes are to learn about some aspects of the social world and to generate new understandings that can be used by that social world. Anthropological qualitative research is about the interpretation of social world especially of cultures and people’s life-ways rather than seeking causal explanations for cultural practices. In anthropological writings as much attempt and consideration should be given to the organization of the scientific paper and article as was given to the execution of the anthropological study, the writer should employ assorted techniques to make the belief, faith based qualitative anthropological study more and more empirical. DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7044 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 123-137